Effect of Annealing Temperature on Electrodeposited Iron Oxide Thin Films for Supercapacitor Study - Vidya S. Shinde; Jagannath V. Thombare; Pranita M. Jondhale; Rameshwar R. Kothawale (International Journal of Scientific Research in Science and Technology, 2025)
Fe2O3 samples were electrodeposited onto stainless steel at 1.4 V optimum potential using a 0.2 M FeCl3 precursor solution. They were then annealed at various annealing temperatures between 673 and 723 K with 50° increments. XRD analysis verifies that a crystalline rhombohedral crystal structure has formed. A consistent porous, spongy, beautiful gold flower-like morphology is demonstrated by the FESEM and HRTEM morphologies, and wettability tests indicate its hydrophilic nature. The 1 M KOH electrolyte was used for all electrochemical characterizations of the electrodes as they were deposited. The maximal specific capacitance of the optimized electrode is 898.52 Fg-1 at 2 mVs-1 . Using the galvanostatic charge-discharge technique, the highest values of specific energy (SE), specific power (SP), and columbic efficiency (ɳ) were determined to be 45.88 WhKg-1 , 5.33 KWKg-1 , and 97.67%,respectively. According to EIS investigations, the internal resistance was 0.7869 Ώ.
Keywords: Iron oxide (Fe2O3); porous; Electrodeposition; Energy and power